Real-world Effectiveness of Tofacitinib for Moderate to Severe Ulcerative Colitis: A Multicentre UK Experience. (13th April 2020) - Honap, Sailish; Chee, Desmond; Chapman, Thomas P; Patel, Mehul; Kent, Alexandra J; Ray, Shuvra; Sharma, Esha; Kennedy, James; Cripps, Sarah; Walsh, Alissa; Goodhand, James R; Ahmad, Tariq; et al.
Abstract: Background: Tofacitinib is a partially selective Janus kinase inhibitor approved for the treatment of refractory moderate to severe ulcerative colitis [UC]. We sought to define the effectiveness and adverse effects of tofacitinib in a real-world cohort. Methods: We conducted a retrospective observational cohort study of 134 patients with UC [64% male; median age 37 years [range 16–81]; 83% of patients had previously received at least one biologic] treated with tofacitinib from October 2018 to October 2019 in four UK centres. Disease activity was assessed using the Simple Clinical Colitis Activity Index [SCCAI] or partial Mayo score [PMS], depending on study site. Response and remission were defined as a reduction in SCCAI or PMS of ≥3and SCCAI ≤2 or a PMS ≤1, respectively. Results: Overall, 74% (88/119; 95 confidence interval [CI] 65–81%] patients responded to tofacitinib at Week 8 and steroid-free remission was observed in 44% [47/108; 95% CI 3453%] patients at Week 26. Primary non-response was independently associated with younger age [ p = 0.014] and higher C-reactive protein [CRP] levels at baseline [ p = 0.004]. Only 23% [3/13] of patients who continued tofacitinib in the setting of primary non-response were in steroid-free remission at Week 26. Prior biologic exposure did not influence response or remission rates. Dose escalation, however, recaptured response in approximately half of patients who had lost response. Dyslipidaemia was observed in 20% [27/134; 95% CI 1428%] of patients, but adverse events necessitating drug withdrawal were uncommon and no venous thromboembolic events occurred. Conclusions: In this multicentre real-world cohort, tofacitinib was well tolerated and clinically effective in a treatment-refractory UC population.